Dunhuang Manuscript Culture. End of the First Millennium - Galambos, Imre (Studies in Manuscript Cultures, 2020)
The book explores the world of Chinese manuscripts from ninth-tenth century Dunhuang, an oasis city along the Silk Roads. It centres around four groups of manuscripts and argues for the existence of a unique local culture combining Chinese and Central Asian elements. The book makes a contribution to the study of cultural and linguistic interaction along the Silk Roads at the end of the first millennium CE.